1985
DOI: 10.1037/0033-2909.97.3.363
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of interpersonal expectancy effects: 31 meta-analyses.

Abstract: This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
344
2
10

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 465 publications
(376 citation statements)
references
References 84 publications
11
344
2
10
Order By: Relevance
“…First, gender stereotypes have important self-fulfilling effects (Harris and Rosenthal, 1985). Hence, they not only affect recruiters, but, through socialisation effects, also female applicants.…”
Section: Why Women May Differ: Gender Stereotypes Multi-income Housementioning
confidence: 99%
“…First, gender stereotypes have important self-fulfilling effects (Harris and Rosenthal, 1985). Hence, they not only affect recruiters, but, through socialisation effects, also female applicants.…”
Section: Why Women May Differ: Gender Stereotypes Multi-income Housementioning
confidence: 99%
“…Research concerned with expectancy confirmation processes focuses on the active role of perceivers in maintaining or creating social reality via their cognitions or behaviors toward a target. (For recent reviews of this literature, see Darley & Fazio, 1980, M. J. Harris & Rosenthal, 1985, and Miller & Turnbull, 1986.) This research has identified two major mechanisms by which a perceiver's expectancies for a target individual or group, even if initially false, may eventually be confirmed.…”
Section: Kay Deaux and Brenda Majormentioning
confidence: 99%
“…The perceiver may communicate his or her expectancies to the target through a variety of mechanisms, including verbal cues, nonverbal cues, and overt action (Harris & Rosenthal, 1985). The exact form the perceiver's behavior takes depends on a number of factors, including his or her goals for the interaction (Miller & Turnbull, 1986).…”
Section: The Perceiver Actsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hedges (1982) and Hunter, Schmidt, and Jackson (1982) suggest that it is inappropriate to include them in one meta-analysis. Harris and Rosenthal (1985) argue that heterogeneity is analogous to individual differences among subjects within single studies, and is common whenever many studies by different investigators using different methods are examined. Hedges (Becker and Hedges, 1984) admitted that: "It is not necessarily inadvisable to draw inferences from heterogeneous effects.…”
Section: Homogeneitymentioning
confidence: 99%